Pitheciid vocal communication: what can we say about what they are saying? - Bezerra, Bruna; Casar, Cristiane; Jerusalinsky, Leandro; Barnett, Adrian; Bastos, Monique; Souto, Antonio; Jones, Gareth (Ethnobiology and Conservation, 2017)
The variation in ecological traits in pitheciids allows investigation of vocal communication over a range of social and acoustic circumstances. In this review paper we present a summary of the history of pitheciid vocal studies and review i) the status of our current knowledge of the vocal repertoire sizes of pitheciid primates, ii) how much do we understand about the context of different acoustic signals and iii) how can we potentially use our knowledge of vocalisations in animal welfare practices. We show trends across taxa and identify gaps in our knowledge. For instance, the repertoires described for Titi monkeys and Sakis have the expected sizes for these genera, considering their relatively small social group sizes. However, Uacari groups can contain over 100 individuals, and a larger vocal repertoire than the ones described would be expected, which could be a consequence of the fission-fusion social system where the large group divides into smaller subgroups. Nevertheless, vocal repertoires exist for only about 12% of the pitheciid species and nothing is known, for example, on call ontogeny. We hope that this review will serve as a reference point for researchers interested in investigating vocal behaviour in this primate group, thus, optimising both funding focus and, researcher’s time and effort. Also, we hope to help defining methodologies and strategies for the conservation and management of pitheciid monkeys.